THE EXTENT TO WHICH STANDARD COSTS CAN BE USED TO RATIONALIZE FINANCIAL NEEDS AN APPLIED STUDY IN THE BAGHDAD SOFT DRINKS COMPANY - Suhair Kadhim Fadhil; Hazim Abed Azeez; Hazem Ali Muttair (Scholar Express Journals, 2022)
The research aims to measure the extent to which the standard costing system can be applied in rationalizing financial needs decisions in the Baghdad Soft Drink Company, As well as measuring the impact of the application of standard costs on the process of controlling the performance of the unit by controlling the various elements of production. In order to explain the research problem and achieve its objectives, the descriptive analytical approach was adopted. Like (50) questionnaires were distributed to the sample members (auditors, accountants, production line managers, and financial analysts), and the simple linear regression model scale tested the research hypotheses. As a result, the research reached the most critical conclusions: Standard costs contribute to making decisions related to financial needs and reducing indirect costs by unit.
Keywords: Standard costs; rationalization of decisions; financial needs